A nested hierarchical perspective to enhance interpretations and communication in fluvial geomorphology for use in water resources management: Lessons from the Okavango Delta, Botswana. Issue 2 (2nd April 2018) - Fryirs, Kirstie A.; Ralph, Timothy J.; Larkin, Zacchary T.; Tooth, Stephen; Humphries, Marc; McCarthy, Terence; Hesse, Paul P.; Mosimanyana, Edwin
Abstract : A key skill that geomorphologists possess is the ability to use multi‐scale perspectives in their interpretations of landscapes. One way to gain these perspectives is with the use of nested hierarchical frameworks. In fluvial geomorphology, such frameworks help with assessment of large‐scale controls (e.g., tectonic activity, climate change) on the pattern and dynamics of smaller‐scale physical features (e.g., channels, floodplains, bars), and conversely illustrate how these smaller‐scale features provide the building blocks from which to make interpretations of fluvial processes and dynamics over larger spatial and temporal scales. Given the rapid pace of technological developments, the range of relatively inexpensive tools available for visualising and mapping landscapes at different spatial scales is expanding exponentially. In this paper, which focuses on the World Heritage‐listed Okavango Delta in Botswana, we demonstrate how various visualisations generated by different technologies at different spatial scales (catchment, landscape unit, reach, site and geomorphic unit) are providing critical baseline information to enhance interpretation and communication of fluvial geomorphology, with potential application in water resources management. In particular, our nested hierarchical approach could be used as an interactive communication tool for non‐specialists and embedded within existing and future management plans for the Delta. The construction of nested hierarchies that synthesise information and analyses can be a valuable addition to the environmental manager's toolkit.